2016
DOI: 10.1088/1612-2011/13/10/106002
|View full text |Cite
|
Sign up to set email alerts
|

Laser ablation efficiency during the production of Ag nanoparticles in ethanol at a low pulse repetition rate (1–10 Hz)

Abstract: We studied the effect of the repetition rate of laser pulses (RRLP) in the range from 1–10 Hz in the production of silver nanoparticles (Ag-NPs) by laser ablation in ethanol. Laser pulses with a duration of 7 ns, a wavelength of 1064 nm and an energy of 60 mJ were used to ablate a 99.99% pure silver target immersed in 10 ml of ethanol. Transmittance analysis and atomic absorption spectroscopy were used to study the silver concentration in the colloidal solutions. The ablation process was studied by measuring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Whereas the shielding of a laser pulse by the self-induced plasma can only be reduced by using shorter pulse lengths, shielding effects induced by previous laser pulses can be reduced procedurally. The strategy is to spatially separate successive laser pulses by adjusting the interplay of the laser spot size, the scanning speed (relative movement between laser beam and target) and the pulse repetition rate to avoid shielding caused by the previous pulse [ 82 , 84 , 90 , 91 , 116 ].…”
Section: Lal Synthesis Methods: Principle Process Parameters and mentioning
confidence: 99%
“…Whereas the shielding of a laser pulse by the self-induced plasma can only be reduced by using shorter pulse lengths, shielding effects induced by previous laser pulses can be reduced procedurally. The strategy is to spatially separate successive laser pulses by adjusting the interplay of the laser spot size, the scanning speed (relative movement between laser beam and target) and the pulse repetition rate to avoid shielding caused by the previous pulse [ 82 , 84 , 90 , 91 , 116 ].…”
Section: Lal Synthesis Methods: Principle Process Parameters and mentioning
confidence: 99%
“…On the other hand, the higher repetition rate (KHz) increases effective ablation due to the greater heat density it creates on the target [42]. Valverde et al [55] have analyzed the effect of RRLP at 1 to 10 Hz on the synthesis of silver nanoparticles (Ag-NPS) by laser ablation in ethanol. The results showed that the efficiency of silver nanoparticles was decreased by reducing the RRLP from 10 to 1 Hz.…”
Section: An Image Of Laser Ablation Of Metals In Liquids During Diffe...mentioning
confidence: 99%
“…For a PRR of 10 Hz and 15 Hz, the diameter of Zn NPs was 12.1 and 5.6, respectively. Similarly, Alva et al [125] investigated the effects of the laser ablation efficiency by varying the PRR (1-10 Hz) of Ag NPs in ethanol. It was shown that the productivity and ablation efficiency of Ag NPs increased with an increase in the PRR.…”
Section: Pulse Repetition Rate (Prr) or Pulse Frequencymentioning
confidence: 99%